Os nós da territorialização da Cooperativa Agroindustrial Lar no Oeste Paranaense - Ben, Marilucia (2011)
The profound changes occurring in the field linked to the expansion of capitalist relations have led to various interpretations about the role of agricultural cooperatives. To understand the cooperative Agroindustrial Lar analysis on the cooperative movement were relevant. In this context, some assumptions are gaining strength, with the transformation of the cooperative system in agro-industry in which consolidated the Agroindustrial Complex. The territorialization and deterritorialization of Agroindustrial Cooperative Home on West Paraná involves mediating relations regarding the process of agricultural modernization, capitalism territorialized in the field, which is essentially contradictory. It is on this issue dealt with in this work, which cut is the geographical western regions that has high rate of incorporation of agricultural modernization in the period 1960 to 1980. Thus the evidence about the mediation process in front of the Cooperativa Agroindustrial Lar agricultural modernization are presented from the intensification of technologies used in rural properties. The theoretical-conceptual territory is developed by many theorists of philosophy, sociology and geography, we turn to discussions of the Swiss geographer Raffestin reflecting on the territory and territoriality in the context of power relations. The "we" of the territorialization of the cooperative study in western regions are related to the meeting point between the relations of society, in this case based on governmental powers, cooperative and religious. The fieldwork on rural properties is based on qualitative research and discuss the overlapping power relations that develop in the field, construction of new territoriality from the mediation of the cooperative.